Properties and structure of cyanate ester/polysulfone/organoclay nanocomposites - Mondragón, I. (2006)
In this paper, a cyanate ester (CE) matrix has been modified with polysulfone and an organic montmorillonite (Nanofil 919). The blend was thermally cured in presence of copper acetylcetonate and nonylphenol. The morphology of the cured materials was investigated by wide angle X-ray, scanning and transmission electron microscopy techniques. An intercalate structure of silicate platelets in the cyanate matrix has been obtained. Furthermore, results of thermogravimetric analysis (TGA) suggest that CE/PSF/Nanofil 919 nanocomposites have higher thermal stability than the neat resin, increasing the onset decomposition temperature. Flexural strength distributions of modified and neat cyanate matrices were obtained by testing the materials in three-point bending. The results were analyzed within the framework of Weibull statistics. The flexural behavior of the resins demonstrated to be sensitive to the intrinsic flaw distribution. The modified system displayed higher fracture toughness and impact strength compared to pure CE. Dynamic mechanical analysis (DMA) studies confirmed that the PSF modified matrix developed a two-phase morphology consisting of spherical PSF dispersed in a thermoset matrix.